DNA barcoding of Sclerogibbidae and confirmation of the opposite sexes of Sclerogibba berlandi Benoit (Hymenoptera: Sclerogibbidae) - Gariepy, Tara; Olmi, Massimo; Guglielmino, Adalgisa; Mita, Toshiharu (Zootaxa, 2022)
The female and male of Sclerogibba berlandi Benoit, 1963 (Hymenoptera: Sclerogibbidae), collected in Abu Dhabi (United Arab Emirates) and characterized by a pronounced sexual dimorphism, were associated for the first time by mitochondrial COI sequences. A comparison with COI sequences of S. crassifemorata Riggio & De Stefani-Perez, 1888 and S. talpiformis Benoit, 1950 from Abu Dhabi proved the diversity of S. berlandi. The COI sequence of a female of S. rossi Olmi, 2005 from Japan, Okinawa-jima, was analyzed for the first time and compared with the other sequences.